Burkitt lymphoma: an unusual location in children, report of a case - Larissa, Midili Tecle; Eurudys, Mekame Meye Angela; Edmee, Mintsa-Mi-Nkama; Claire, Loembe Fifi; Raissa, Koumba Maniaga; Mariela, Lembet Mikolo Aude; Francois, Ntoutoume; Solenge, Solmeheim; Eliane, Kuissi Kamgaing; Simon, Ategbo (International Journal of Contemporary Pediatrics, 2025)
Burkitt lymphoma (BL) is the most common malignant non-Hodgkin lymphoma in African children. It is a very aggressive lymphoma characterized by a high degree of proliferation. If left untreated, the outcome is quickly fatal. The aim of this work is to present an unusual location of BL. We report the case of an 11-year-old patient with bilateral ocular swelling that has been developing for 2 months associated with swelling spread over the entire body in the form of papules and nodules associated with a deterioration in general condition. A paraclinical assessment, namely orbital magnetic resonance imaging (MRI), revealed an enhanced tumor process in the bilateral upper-lateral eyelid orbital regions and the right supra-nasal paramedian facial soft tissues, diffuse filling of the sinuses, diffuse meningeal enhancement of the peri-brain dura; and histology of a nodule confirmed BL. We reported a case of BL with an unusual ocular and cutaneous presentation, which caused a delay in diagnosis and treatment, thus endangering the vital prognosis of our patient.